STRATEGI KOMUNIKASI POLITIK MUHAMMAD DI MADINAH - Ayu Usada Rengkaningtias (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2017)
The influence of the Prophet Muhammad as the bearer of the Islamic message is known plural. It is also about his prophetic and apostolic. The thing that is rarely discussed is Muhammad's position as a political communicator. In this case Muhammad is certainly an actor in the process of political communication in Medina. History calls the long journey of forming the Medina State under the reign of Muhammad starting from zero to become an area that was calculated at that time. It is not excessive for Muhammad to be called as a political actor in the establishment of Medina as well as political communicator in the government of Medina. In political communication, it is mentioned that political actors can form a public opinion, which then becomes consensus and mutually agreed. Thus, Muhammad has fulfilled that element in his leadership over Medina. In the process of political communication, there are important elements such as political communicators, messages delivered, and targets to the political communication effect that made Muhammad in Medina. The interesting thing for studied is Muhammad's political communication strategy. Where is as a political communicator, Muhammad was able to unite the heterogeneity and pluralism of the community who then agreed and want to be under his leadership in Medina. This paper is a literature study with an analytical descriptive approach as a way of describing and explaining historical facts relating to the role of Muhammad as a political communicator. From the results of the research, it was found that Muhammad had a brilliant political communication strategy. These strategies are: 1) The credibility of political communicators; 2) Create culture together and the elimination of racism as a political message; 3) Medina Charter as a target of political communication; 4) The practice of negotiation in political communication; 5) Selection of appropriate media in political communication. The entire political communication strategy of Muhammad can be seen from the elements of political communication. The author mentions that the Prophet Muhammad as the leader of Medina at that time has a communication strategy that goes far beyond the existing contemporary theory.